STUDI PENGARUH SISTEM INFORMASI AKUNTANSI, SISTEM PENGENDALIAN INTERNAL DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN PT. MUJUR TIMBER DI MEDAN - SIJABAT, JADONGAN; LESTARY S, ANGELY AYU (Jurnal Riset Akuntansi & Keuangan, 2022)
The objectives of this study are: 1) to determine the effect of accounting information systems on the quality of financial statement. 2) to determine the effect of the internal control system on the quality of financial statement, 3) to determine the effect of human resource competence on the quality of financial statement. Research data were collected using a questionnaire to 35 employees at PT. Mujur Timber in Medan. The sampling technique used is the saturated sample. Data were analyzed using multiple regression analysis with the help of SPSS version 25 program. The results showed that the accounting information system had a significant effect on the quality of financial statement, the internal control system had a significant effect on the quality of financial statement, and the competence of human resources had a significant effect on the quality of financial statement.